Single-dose fosaprepitant for the prevention of chemotherapy-induced nausea and vomiting in patients receiving moderately emetogenic chemotherapy regimens: a subgroup analysis from a randomized clinical trial of response in subjects by cancer type - Weinstein, Cindy; Jordan, Karin; Green, Stuart; Khanani, Saleem; Beckford-Brathwaite, Elizabeth; Vallejos, Waldimir; Pong, Annpey; Noga, Stephen J.; Rapoport, Bernardo L. (BMC cancer, 2020)
Background Results from a phase III, randomized, double-blind, active comparator-controlled, parallel-group trial evaluating fosaprepitant for the prevention of chemotherapy-induced nausea and vomiting (CINV) found that a single-day, triple-antiemetic fosaprepitant regimen resulted in a significantly higher proportion of patients achieving a complete response (CR; no vomiting or rescue medication use) in the delayed phase (25–120 h after chemotherapy initiation), compared with a 3-day control regimen ( ClinicalTrials.gov , NCT01594749). As the risk for CINV is dependent on chemotherapy regimen and generally guided by tumor type, this post hoc analysis evaluated the efficacy and safety of this regimen by cancer subpopulations (gastrointestinal [GI] or colorectal, lung, breast, and gynecologic cancers). Methods Subjects with confirmed cancer who were naive to highly and moderately emetogenic chemotherapy (HEC and MEC) and were scheduled to receive intravenous (IV) anthracycline-cyclophosphamide (AC)–based MEC on the first day of chemotherapy were randomly assigned to receive oral ondansetron and oral dexamethasone plus either a single IV dose of fosaprepitant 150 mg (fosaprepitant regimen) or placebo (control regimen). The primary efficacy end point was the proportion of subjects achieving CR in the delayed phase. CR rates in the overall and acute phases (0–120 h and 0–24 h after MEC initiation, respectively) were assessed as secondary end points. Safety and tolerability were also assessed. Results CR rates in the delayed phase favored the fosaprepitant regimen over the control regimen across the GI/colorectal, lung, breast, and gynecologic cancer subgroups (range, 6.2–22%); similar findings were observed for CR in the overall phase. CR in the acute phase was high for all groups (≥87%). The fosaprepitant regimen was well tolerated in all cancer subgroups. Conclusions This post hoc analysis indicated that a single-day fosaprepitant regimen was effective in preventing CINV in patients receiving MEC, regardless of cancer type. Trial registration ClinicalTrials.gov NCT01594749 , registered May 9, 2012.